The Party's Over: The Role of Earnings Guidance in Resolving Sentiment-Driven Overvaluation - Yang, I-Hwa (Institutional Knowledge at Singapore Management University, 2012)
This paper shows that an important link between investor sentiment and firm over valuation is optimistic earnings expectations, and that management earnings guidance helps resolve sentiment-driven overvaluation.Using previously identified firm characteristics, we find that most of the negative returns to uncertain firms in months following high-sentiment periods fall within the three-day window around the issuance of management earnings guidance. Comparisons of guidance months to nonguidance months show that guidance issuance affects the magnitude and not just the daily distribution of negative returns. There is also some evidence of negative returns around earnings announcements for firms that previously issued guidance, suggesting that guidance does not entirely correct optimistic earnings expectations. To provide additional insight into the strength of the guidance effect, we show that the market reacts more strongly to surprises, particularly negative surprises, following high-sentiment periods. Finally, firms with higher transient institutional ownership are less likely to guide, and their guidance is less likely to contain bad news following high-sentiment periods,indicating that managers with a short-term focus are hesitant to correct optimistic market expectations.